2008
DOI: 10.1021/op700288p
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Robust Ring-Closing Metathesis Reaction in the Synthesis of SB-462795, a Cathepsin K Inhibitor

Abstract: The development of a robust and high-yielding ring-closing metathesis (RCM) reaction and its demonstration on multikilogram scale are described. A detailed understanding of the impact of impurities on the RCM reaction was achieved using a variety of chemical and statistical methods. Specifically, individual impurities were evaluated in spiking studies to identify those that negatively affected the RCM reaction. Projection methods (PCA and PLS) were applied to historical data to identify the main sources of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…However, supported catalysts have a few drawbacks, some of which are high catalyst loadings, low turnover numbers and tedious synthetic procedures. There have also been numerous attempts to reduce the ruthenium content in metathesis products by homogeneous work-up techniques-chromatography 21 , chemical transformations 22 , scavenging ruthenium residues using phosphines 23 (more than 10 equiv.) or 50 equiv.…”
mentioning
confidence: 99%
“…However, supported catalysts have a few drawbacks, some of which are high catalyst loadings, low turnover numbers and tedious synthetic procedures. There have also been numerous attempts to reduce the ruthenium content in metathesis products by homogeneous work-up techniques-chromatography 21 , chemical transformations 22 , scavenging ruthenium residues using phosphines 23 (more than 10 equiv.) or 50 equiv.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] ForRumetathesis catalysts,both Brønsted and Lewis base functionalities are now known to be problematic ( Figure 3; see also Section 2.4). [11][12][13][14][15] ForRumetathesis catalysts,both Brønsted and Lewis base functionalities are now known to be problematic ( Figure 3; see also Section 2.4).…”
Section: Impact Of Impuritiesmentioning
confidence: 99%
“…[28] Process robustness was agreater challenge.Aphosphine-free catalyst (HII)was found to be essential at the discovery stage.O ns cale-up, however, the catalyst loadings required for complete conversion varied dramatically from batch to batch. [14] An impurity profile analysis (spiking with potential poisons,accompanied by multivariate analysis), revealed that 13 and 14 (Figure 11 c) were principally responsible.Urea 13 is ab yproduct of sulfonamide installation;a mide 14 forms during aqueous workup prior to RCM. Considered as potential culprits were DBU and phosphazene base (Figure 3), and ar ange of basic sideproducts containing as econdary amine or urea functionality.…”
Section: Cathepsin Inhibitorsmentioning
confidence: 99%
“…While increased temperatures have previously shown to improve metathesis efficiency,6c,9 temperatures above 55°C decreased assay consistency and resulted in solvent losses. To minimize introducing experimental errors into the system, all assays were carried out at 50 °C which was the best compromise between fast reaction rates and solvent loss.…”
mentioning
confidence: 99%